Formation of nickel-silica gels structure in the conditions of thermal- and hydrothermal processing - Косенко, Олена Іванівна; Кустовська, Антоніна Дмитрівна (Eastern-European Journal of Enterprise Technologies, 2013)
Silica gel-based binary jointly precipitated oxide-hydroxide systems can be considered as perspective adsorbents and blank substrates for catalytic active substances in which both regulation of porous structure and acid-base properties of surface are possible due to the presence of metal oxide. In the paper the systematic investigation of influence of jointly precipitated NiO:SiО2 systems composition and conditions of their thermal and hydrothermal modification on porous structure of nickel-silica gels and their phase composition has been conducted. It has been shown that hydrothermal processing provides more opportunities for regulation of the porous structure than thermal processing, besides after hydrothermal modification nickel-silica gels have higher thermostability, which is important for their use in the high-temperature catalytic processes. The samples of nickel-silica gels with values of specific surface area 20-550 m2/g, sorption volume of pores 0,1-0,8 cm3/g, diameter of pores 20-800 Ǻ and various phase composition were synthesized, that opens wide prospects for their application. The revealed laws were explained by combined action of mass transport and phase transformations and mutual influence of the components on these processes